All Days 2011
DOI: 10.2118/139623-ms
|View full text |Cite
|
Sign up to set email alerts
|

Drilling Fluid Design Enlarges the Hydraulic Operating Windows of Managed Pressure Drilling Operations

Abstract: With the increasing use of Managed Pressure Drilling (MPD) to mechanically control bottomhole pressures for drilling narrow mud-weight windows, little consideration has been given until recently to integrating drilling fluid design and MPD operations for a specific application. This paper describes how two converging technologies have emerged in recent years that both converge on more effectively managing narrow hydraulic operating windows in extended reach, horizontal, and through tubing drilling operations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The possibility of fracturing the formation, leading to loss circulation, made it critical to optimize the fluid performance and stay within the narrow operating window. Use of TMB assists in reducing the ECD and thus effectively enlarging the operating window (Oakley and Conn 2011). The operating window for the field trial in Brazil is shown in Figure 2; the operating window is the area between the pore pressure (blue line) and the fracture gradient (brown line).…”
Section: Hydraulic Operating Windowmentioning
confidence: 99%
“…The possibility of fracturing the formation, leading to loss circulation, made it critical to optimize the fluid performance and stay within the narrow operating window. Use of TMB assists in reducing the ECD and thus effectively enlarging the operating window (Oakley and Conn 2011). The operating window for the field trial in Brazil is shown in Figure 2; the operating window is the area between the pore pressure (blue line) and the fracture gradient (brown line).…”
Section: Hydraulic Operating Windowmentioning
confidence: 99%
“…Take the drilling as an example, with the increase of slim hole, complex structure wells and the drilling depth, the requirement of hydraulic calculation accuracy is more and more high, especially with the implementation and promotion of management pressure drilling technology in the narrow density window formation [1][2][3]. Because the annular conditions of the drilling engineering are complex and annular pressure loss is influenced by many factors, the annular hydraulic calculation accuracy is difficult to meet the requirements.…”
Section: Introductionmentioning
confidence: 99%